2016
DOI: 10.1088/0031-9155/61/7/2802
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of intrinsic rise times for various L(Y)SO and LuAG scintillators with a general study of prompt photons to achieve 10 ps in TOF-PET

Abstract: The coincidence time resolution (CTR) of scintillator based detectors commonly used in positron emission tomography is well known to be dependent on the scintillation decay time (τd) and the number of photons detected (n'), i.e. CTR proportional variant √τd/n'. However, it is still an open question to what extent the scintillation rise time (τr) and other fast or prompt photons, e.g. Cherenkov photons, at the beginning of the scintillation process influence the CTR. This paper presents measurements of the scin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
144
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 49 publications
0
144
0
Order By: Relevance
“…Laboratory results already have demonstrated timing of under 100 ps under idealized conditions (56), and as sensors, scintillators, and detector designs continue to improve, we can anticipate that the timing performance of scanners will continue to get better. Looking even farther into the future, it may be possible to exploit prompt mechanisms, instead of relying on the relatively slow production of scintillation light, to generate signals in detectors that could obviate image reconstruction and provide event coordinates directly (57,58). This possibility, however, would require a timing resolution on the order of 20 ps to achieve 3-mm spatial resolution.…”
Section: Timing Resolutionmentioning
confidence: 99%
“…Laboratory results already have demonstrated timing of under 100 ps under idealized conditions (56), and as sensors, scintillators, and detector designs continue to improve, we can anticipate that the timing performance of scanners will continue to get better. Looking even farther into the future, it may be possible to exploit prompt mechanisms, instead of relying on the relatively slow production of scintillation light, to generate signals in detectors that could obviate image reconstruction and provide event coordinates directly (57,58). This possibility, however, would require a timing resolution on the order of 20 ps to achieve 3-mm spatial resolution.…”
Section: Timing Resolutionmentioning
confidence: 99%
“…This digital silicon photomultiplier (dSiPM) array allows triggering on the first detected photon , Gundacker et al 2016b. Additionally, the DPC array provides a validation cycle that can be used to reject unwanted triggers resulting from dark counts.…”
Section: Equation (mentioning
confidence: 99%
“…Specifically, an undoped LuAG crystal with a size of 3 mm × 3 mm × 8 mm was used. It was reported that pure LuAG shows mainly Cherenkov emission upon excitation of 511 keV annihilation photons and thus is a good candidate to estimate the IRF including the photon travel time spread within the crystal (Lecoq et al 2010, Brunner 2014, Gundacker et al 2016b. The crystal was black-taped and coupled to the SPAD with optical grease (BC-630) and to the stop-pixel with Cargille Meltmount 1.528, in the same way as the BGO crystals under test (see figure 3).…”
Section: Rise Timementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, free carrier capture centers might additionally delay the population of luminescent centers. The rise time of scintillation development might be exploited for substantial shifting the time resolution to picosecond and sub-picosecond domain [10], as seeked for in many future applications. One of the novel approaches to substantially improve the time resolution is splitting the detection into the readout of the moment of irradiation interaction with the scintillator to ensure high time resolution and the readout of the amplitude of the scintillator response carrying information on the deposited energy of ionizing radiation (see [11] and references therein).…”
Section: Introductionmentioning
confidence: 99%